2004
DOI: 10.1002/eji.200425563
|View full text |Cite
|
Sign up to set email alerts
|

Effector and regulatory T cells derived from the same T cell clone differ in MHC class II‐peptide multimer binding

Abstract: MHC class II-peptide multimers are a valuable tool for antigen-specific detection of CD4 + T cells. However, it has been proposed that T cells in a hypo-responsive state can have diminished binding of such multimers. In the present study, we investigated this phenomenon at the clonal level. We found that anergic CD4 + T cells had a reduced capacity to bind MHC class II-peptide multimers compared to their non-anergic counterparts. Increasing the incubation temperature, time, or MHC-peptide valency could not equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…These results are in agreement with 2 earlier studies describing reduced HLA/peptide multimer binding by T REG . 17,18 Low avidity CD8 dim staining HY-specific T REG have been described in a murine allograft tolerance model. 30 These observations collectively point to incomplete T-cell receptor signaling as a common feature of T REG function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with 2 earlier studies describing reduced HLA/peptide multimer binding by T REG . 17,18 Low avidity CD8 dim staining HY-specific T REG have been described in a murine allograft tolerance model. 30 These observations collectively point to incomplete T-cell receptor signaling as a common feature of T REG function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, differences in tetramer staining intensity may indicate the presence of functionally different types of T cells. 17,18 The dominant presence of minor H antigen-specific alloimmune T REG or T CTL in a hematopoietic stem cell (SC) graft may have differential impacts on the outcome of HLA identical minor H antigen nonidentical stem cell transplantation (SCT). As a first step toward understanding how the minor H antigen alloimmunization status of SC donors may affect SCT outcome, we analyzed whether "natural" exposure to fetal or maternal minor H alloantigens induces functionally different T cells in healthy parous female and male blood donors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that short-term culture of PBMCs with the presence of specific antigen may increase the number of antigenspecific T cells and facilitates tetramer staining, flow cytometry cell sorting, and tracking of these T cells during viral infections [22][23][24][25][26][27]. Culture temperature and activation status of these T cells may also affect the efficiency of tetramer staining [25][26][27].…”
Section: Study Subjectsmentioning
confidence: 98%
“…Amino acids that are regarded as having a negative effect on the binding ability are given values between )1 and )3. The 17 peptides with 15-mer amino acids used in this study were arbitrarily designed (their SYFPEITHI scores not shown, Supplementary Table 1), of which, P2, LSFLPSDFFP SVRDL (HBcAg [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ) and P13, PPAYRPPNAPILSTL (HBcAg 129-143 ) had the highest SYFPEITHI scores, i.e., 20 and 28, for DRB1*0401 and DRB1*0101 molecules, respectively. They were used for the construction of each of MHC class II tetramers.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation